2018
DOI: 10.4337/roke.2018.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Inflation targeting when devaluations are contractionary

Abstract: In the New Consensus model, when monetary policy is sufficiently sensitive to changes in the rate of inflation, a standard Taylor rule can effectively pin down inflationary expectations and stabilize the economy at practically no output cost. It is often believed that assuming an open or a closed economy does not matter. This view is incorrect, and the result depends critically on the nature of devaluations. When devaluations are contractionary, standard Taylor rules do not work. This result holds in a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…11 In an open economy set-up, contractionary effects from depreciations, associated for example with the balance sheet effect (as in Céspedes et. al., 2004) or redistribution from wage income to profits and rents (Díaz-Alejandro, 1965) may imply that output and inflation are also not pinned down by a standard Taylor Rule (Libman, 2018). Indeed, with strong contractionary effects from depreciations, the sudden opening of the capital account may lead to a strong initial exchange rate appreciation, and some expansionary effects on the non-tradable sector may emerge.…”
Section: The Elimination Of the Fx Controlsmentioning
confidence: 99%
“…11 In an open economy set-up, contractionary effects from depreciations, associated for example with the balance sheet effect (as in Céspedes et. al., 2004) or redistribution from wage income to profits and rents (Díaz-Alejandro, 1965) may imply that output and inflation are also not pinned down by a standard Taylor Rule (Libman, 2018). Indeed, with strong contractionary effects from depreciations, the sudden opening of the capital account may lead to a strong initial exchange rate appreciation, and some expansionary effects on the non-tradable sector may emerge.…”
Section: The Elimination Of the Fx Controlsmentioning
confidence: 99%
“…A partir de 2016, el banco central adoptó un régimen de metas de inflación inconsistente con la política fiscal contractiva que implicó, dada su configuración, un aumento de la tasa de inflación. En este contexto, las expectativas cambiaron abruptamente llevando a devaluaciones que resultaron en recesión y alta inflación (Libman, 2018). En este trabajo se mostrará que los shocks de incertidumbre son relativamente importantes y pueden ser otro factor a la hora de explicar el desempeño macroeconómico de Argentina.…”
Section: Introductionunclassified
“…The hypothesis that devaluations have contractionary effects was formulated during a period were fixed exchange rate and low capital mobility was the norm (Diaz Alejandro, 1963, 1965Krugman and Taylor, 1978), but there are good reasons to believe that the contractionary effects have not disappeared Although exchange rate regimes are much more flexible than in the past, central banks intervene very often in the foreign exchange market to avoid undesirable exchange rate fluctuations Moreover, as documented by Barbosa-Filho (2015) and Ros (2015) for the cases of Brazil and Mexico, monetary policy has been used to prevent large depreciations, but fewer interventions have been conducted to avoid appreciations (Libman, 2018a) This suggest that policy makers in those countries fear the negative repercussions of large exchange rate depreciations, but they welcome the expansionary effects from appreciations Consider the case of Brazil during the last decades When the real exchange rate depreciated, 1 inflation accelerated, while output remained stagnant, both during 1 In this paper we follow the Latin American convention We define the nominal exchange rate as the number of units of the domestic currency that are needed to buy a unit of the foreign currency A depreciation means that the exchange rate goes up, and so on Because the original literature on 2002-2003, and more recently, in 2014-2016 (Serrano and Summa, 2016) Although factors such as fiscal policy and terms of trade were probably at play, this suggests that depreciations have contractionary effects Galindo and Ros (2008) explored the recent Mexican case Using VAR analysis, they found that devaluations have a weak contractionary effect on output, at least in the short-run Both Brazil and Mexico have experienced slow growth In contrast, the Peruvian economy has been performing quite well; growth has been fast, while inflation has remained low and stable Peru is well-known for its highly dollarized financial system and the Inflation Targeting regime that was adopted during the early 2000s was designed on the assumption that devaluations reduce output Because exchange rate depreciations exert a negative effect on the balance sheet of banks, the Taylor Rule was complemented with frequent interventions in the foreign exchange market, as well as with other unconventional monetary policy tools (such as reserve requirements for dollar denominated deposits), to curtail excessive exchange rate volatility Inspired by the different performance of main Latin American economies that have adopted Inflation Targeting, this paper ask what are the implications associated with the presence of contractionary effects of depreciations when Inflation Targeting is operative 2 To understand the nature of the problem, consider for example a shock that implies appreciation of the nominal exchange rate that translates into a real appreciation (which is the case if inflation is low or moderate, see Taylor and Taylor, 2004) If demand depends negatively on the real exchange rate, the most likely case when depreciations are contractionary, then the appreciation generates further demand pressures Because the increase in demand may generate some pressures on output and employment and consequently on prices, or because the central bank also includes the output...…”
Section: Introductionmentioning
confidence: 99%